The establishment of lipid profiles reference ranges during pregnancy: a systematic review and meta-analysis - Liyun Sun; Bingrui Gao; Mingyue Wang; Yuqi Liu; Zhongyan Shan; Weiping Teng; Dongdong Luo; Jing Li (Reproductive Biology and Endocrinology)
Abstract Background Maternal lipid levels, which are crucial for both foetal development and maternal health, exhibit significant physiological changes during pregnancy. Current reference ranges for lipids that are based on common adults may inadequately assess the appropriate lipid levels during pregnancy and fail to predict potential risks. Therefore, it is necessary to establish trimester-specific reference intervals (TSRIs) for pregnant women during pregnancy. Objective To establish TSRIs for total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-c, and low-density lipoprotein cholesterol (LDL-c) levels during pregnancy and to explore potential factors influencing lipid levels. Methods Following PRISMA/MOOSE guidelines, 13 observational studies (54,517 healthy women with singleton pregnancies) were included and analyzed. The pooled means and associated 95% confidence intervals (95% CIs) were calculated using a random effects model, and the TSRIs for women with singleton pregnancies were calculated using a frequentist approach. The quality of the included studies was appraised by the Agency for Healthcare Research and Quality (AHRQ) scale. Results The established TSRIs for the women with singleton pregnancies during the first, second, and third trimesters were 3.00–5.83, 3.79–7.87, and 4.39–8.98 mmol/L for TC; 0.08–2.27, 0.39–3.90, and 0.82–5.00 mmol/L for TG; 0.86–2.34, 0.80–2.69, and 0.83–2.58 mmol/L for HDL-c; and 1.16–3.56, 1.51–5.04, and 1.90–5.74 mmol/L for LDL-c, respectively. The TSRIs applicable to Chinese women with singleton pregnancies were 2.96–5.66, 3.79–7.63 and 4.36–8.69 mmol/L for TC; 0.22–2.05, 0.56–4.08 and 1.10–5.15 mmol/L for TG; 1.01–2.35, 0.84–2.66 and 0.67–2.72 mmol/L for HDL-c; and 1.12–3.38, 1.39–4.94 and 1.79–5.60 mmol/L for LDL-c for the first, second, and third trimesters. Compared with pregnant women from Asia, European and South American pregnant women showed higher serum third-trimester TC level and lower second-trimester TG and third-trimester TG and LDL-c levels. Studies using enzyme colorimetry method reported higher second-trimester TG and third-trimester TG and HDL-c levels than those using enzyme methods. In addition, the third-trimester TC, HDL-c, LDL-c and three-trimesters TG levels were significantly higher as reported by the studies conducted before 2015 than by the ones conducted after 2015. Conclusion The appropriate establishment of TSRIs is essential for accurate diagnosis of dyslipidaemia during pregnancy, which may be affected by the inhabited regions where pregnant women lived, the assay methods and the years when study conducted. Further region-specific and method-specific TSRIs for women with singleton pregnancies using the latest data are needed in order to enhance the diagnostic capability of dyslipidaemia in pregnant women during three trimesters.